Effect of Ultrasonic Extract of Capparis spinosa‎‎ Fruits Against E. coli‎‎ O157:H7‎ - N Abdulridha, Reham; H Saliem, Ali (The Iraqi Journal of Veterinary Medicine, 2023)
E. coli‎‎ O157:H7, is one of the main causes of diarrhea and the most prevalent bacterial ‎infection that causes serious illnesses. This research was conducted to investigate the effect of Capparis ‎spinosa fruit ultrasonic extract against resistant E. coli‎‎ O157:H7 was isolated from stools of calves ‎that were suffering from diarrhea; the bacteria were identified by the Vitek 2 system and a latex agglutination ‎test. C. spinosa‎‎‎ was extracted by ultrasonic waves water bath. The phytochemicals were carried out on C. ‎spinosa fruit extract to detect the secondary metabolites. The MIC of the extract was calculated with ‎concentrations of 400, 800, 1600, 3200, 6400, 12800 and 25600 51200 µg/mL by microdilution method ‎‎(checkerboard). While using a field-emission scanning electron microscope to observe the morphological ‎alterations in E. coli‎‎ O157:H7 sample. The findings of this study revealed that the extract contains some ‎biologically active compounds like alkaloids, flavonoids, steroids, glycosides, tannins, cumarines, saponins, ‎quinones, and amino acids. That extract of C. spinosa‎‎‎ had a MIC of 6400 µg/mL and had a perfect action ‎against E. coli‎‎. O157:H7 by forming vacuoles within the cells and that internal content had seeped out as pore ‎formation. This finding could potentially provide an explanation for the traditional utilization of ‎this plant material as an antibacterial agent‎‎.